Design of cold-formed steel single C-section portal frames. (November 2019) - Rinchen; Rasmussen, Kim J.R.; Zhang, Hao
Abstract: This paper presents design approaches for cold-formed steel single C-section portal frames based on the Direct Strength Method and the Direct Design Method. For the Direct Strength Method, two approaches are presented, one that determines the design capacity of portal frames ignoring the effect of bimoment, as in current practice, and one that considers the effect of bimoment. The Direct Design Method determines the frame strength directly using geometric and material nonlinear analysis, also referred to as Advanced Analysis. The frame capacities predicted by the Direct Design Method and the conventional Direct Strength Method are found to agree well with frame capacities obtained from recent full-scale frame tests. To derive the system resistance (capacity) factor for cold-formed steel portal frames, a system reliability analysis is carried out with statistical parameters for system strength derived from six full-scale frame tests and corresponding system strengths predicted by Advanced Analysis. Highlights: Design approaches for cold-formed steel portal frames using Direct Strength Method and Direct Design Method are presented. The influence of bimoment on the capacity of members in CFS portal frames is detailed. Design by the Direct Design Method using three-dimensional shell finite element models for CFS portal frames is outlined. A system reliability analysis is conducted to derive resistance factors for CFS portal frames.